Reciprocal projections between the globus pallidus externa and cortex span motor and nonmotor regions - Emily A. Ferenczi; Wengang Wang; Anushka Biswas; Trent Pottala; Yihuan Dong; Alison K. Chan; Madeline A. Albanese; Raina S. Sohur; Tingying Jia; Kevin J. Mastro; Bernardo L. Sabatini (Proceedings of the National Academy of Sciences, 2025)
The globus pallidus externa (GPe) is a heterogeneous nucleus of the basal ganglia, with intricate connections to other basal ganglia nuclei, as well as direct connections to the cortex. The anatomic, molecular, and electrophysiologic properties of cortex-projecting pallidocortical neurons are not well characterized. Here, we show that pallidocortical neurons project to diverse motor and nonmotor cortical regions, are organized topographically in the GPe, and segregate into at least two distinct electrophysiological and molecular phenotypes. In addition, we find that the GPe receives direct synaptic input from deep layers of diverse motor and nonmotor cortical regions, some of which form reciprocal connections onto pallidocortical neurons. These results demonstrate the existence of a fast, bidirectional circuit between the GPe and the cortex that is ideally positioned to integrate information about behavioral goals, internal states, and environmental cues to rapidly modulate behavior.